2021
DOI: 10.1111/febs.16088
|View full text |Cite
|
Sign up to set email alerts
|

A guide to genetically encoded tools for the study of H2O2

Abstract: Cell metabolism heavily relies on the redox reactions that inevitably generate reactive oxygen species (ROS). It is now well established that ROS fluctuations near basal levels coordinate numerous physiological processes in living organisms, thus exhibiting regulatory functions. Hydrogen peroxide, the most long-lived ROS, is a key contributor to ROS-dependent signal transduction in the cell. H 2 O 2 is known to impact various targets in the cell, therefore the question of how H 2 O 2 modulates physiological pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 125 publications
2
15
0
Order By: Relevance
“…This disagreement suggests that the role of the active sites in the form of V ). This is consistent with the observation that H 2 O 2 is the most longlived ROS 101 and so induces considerable cytotoxicity on cancer cells. 102,103 However, the effect of the medium is clear in that the cell viability at 48 h decreased to 35 ± 2%.…”
Section: Cytotoxicity Of Nanoceria Against Tumor Cells and Normal Cellssupporting
confidence: 92%
“…This disagreement suggests that the role of the active sites in the form of V ). This is consistent with the observation that H 2 O 2 is the most longlived ROS 101 and so induces considerable cytotoxicity on cancer cells. 102,103 However, the effect of the medium is clear in that the cell viability at 48 h decreased to 35 ± 2%.…”
Section: Cytotoxicity Of Nanoceria Against Tumor Cells and Normal Cellssupporting
confidence: 92%
“…The CCK8 results demonstrated that tetrapeptide exhibited good biocompatibility even at the concentration 6 mg/mL (Figure c). One of the major advantages of mimetic tetrapeptide is the ease of use without a priori genetic manipulations . To demonstrate the suitability of the CFFH tetrapeptide for detecting hydrogen peroxide in acidic organelles, we pretreated the HeLa cells with tetrapeptide for 24 h. The confocal laser scanning microscopy (CLSM) revealed that weak blue fluorescence and a visible green spot were observed in the cells, which suggested that the roGFP2 mimetic tetrapeptide could monitor hydrogen peroxide in an acidic microenvironment (Figure d).…”
Section: Resultsmentioning
confidence: 99%
“…Later, several H 2 O 2 sensors were developed by fusing roGFP or rxYFP to thiol-based peroxidases, such as Orp1, 389 Tsa2, 390 Prx1 391 and Tpx1. 392,393 The peroxidases oxidise the cysteine pair on the roGFP later react with H 2 O 2 .…”
Section: Genetically Encoded Fluorescent Probesmentioning
confidence: 99%